Architecture of the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mulaprasada (main shrine) has a mukhamandapa (front porch), antarala (vestibule or antechamber), and garbhagriha (sanctum sanctorum). The pillared hall is open with a pyramidal shikhara (superstructure). It leads to the antarala and the garbhagriha is a pancharatha (with five rathas or projections on each side) structure with a latina shikhara (mono-spired superstructure) which comprises a sukanasa (antefix above the roof of the kapila) at the front, an amalaka (a crowning member of the latina shikhara shaped like a myrobalan fruit) and a kalasha (pitcher finial) at the top.